PENGARUH POLA ASUH TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN DI KOTA SERANG - Alis Triena Permanasari; Ratih Kusumawardani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
Developing creativity is a long term process that should be started early. Appropriate stimulations needed to determine 80% brain development in a first 6 years of human life. Parents are the first environment where the chidren could grow their creativities and other potential. The research’s goal is to gain the information about the effects of parenting role towards 5-6 years old children creativity in Serang Banten. This research using survey methods with a sample size of 36 children and their parents. Sample taken randomly from all Kindergartens in 6 Kecamatan in Serang Banten. Data were analyzed using SPSS one way ANOVA. The study showed that children creativity from permissive parenting is higher than authoritarian and authoritative parenting, despite this does not indicate a significant effect between parenting style towards creativity. This may happen because the parents can not simply implementing one parenting in order to optimize creativity. Parents should implementing parenting style equally and it must be adjusted to the level of development and the uniqueness of each child. Research hypothesis is rejected may occur due to other factors. Other factors which thought to affect the development of children’s creativity such as parent education background, parents’ job, child birth order, and sex. Thus, researchers can conclude that the findings in the study showed no significant effect between parenting with 5-6 years old children creativity in Serang Banten.